Membrane potential and intracellular cyclic AMP as regulators of calcium homeostasis in formyl peptide-activated human neutrophils : lessons from chronic granulomatous disease - Anderson, Ronald (University of Pretoria, 2013)
Thesis (DPhil (Immunology))--University of Pretoria, 2005.